Pondok Pesantren Dalam Menghadapi Perubahan Zaman - qiyadah robbaniyah; Roidah Lina (J-Alif : Jurnal Penelitian Hukum Ekonomi Syariah dan Budaya Islam, 2023)
Islamic boarding schools in carrying out their functions as educational institutions that are involved in educating the nation, must have the resilience or ability to answer the needs of the times. The Bin Baz Islamic Center Islamic Boarding School as an Islamic educational institution which has increased every year in the acceptance of new students and consistently carries out innovations and new breakthroughs in running the organization and educational process at the Islamic boarding school, the researchers want to explore in depth how the Bin Baz Islamic Center Islamic Boarding School in the face of changing times. This research method is a qualitative research, a type of case study research, namely a case study at the Islamic Center Bin Baz Yogyakarta Islamic Boarding School in dealing with changing times. Data collection methods used are interviews, observation and documentation. The data analysis used describes the data obtained and then classifies it into groups, finally analyzing the data obtained. The results of this study are that in facing the changing times, the Bin Baz Islamic Boarding School has made several changes both internally and externally at the pesantren. In its journey, the Bin Baz Islamic Center Islamic Boarding School made breakthroughs and continued to innovate to exist and maintain the quality of graduates. The Bin Baz Islamic Center Islamic Boarding School has a superior target, namely "ABATA", a distinctive feature and superior target is having the correct creed in active Arabic and being able to understand bare books, having good morals, tahfizh al-Qur'an with good tahsin, achieving academically. The Bin Baz Islamic Center Islamic Boarding School divides the management/management of the pesantren into 3 (three) parts, namely: KBM (Teaching and Learning activities) at school, Tahfidz (Halaqoh Tahfidz), Kesantrian (dormitory, kitchen, cleanliness, tarbiyah, language, UKP, worship, security , sapras, finance, etc.). Management of Changes made in Islamic Boarding Schools is divided into several parts, namely: first: HR (Human Resources) Performs Standardization of existing Human Resources from school teachers, Tahfidz Teachers, Dormitory Management, Educators, Security Guards, Cleaning staff, and all those involved in Management of Islamic Boarding Schools. Second: Building a System for Each Section, third: Infrastructure and Financial Facilities, fourth: Following developments in market needs in the implementation of education in Islamic boarding schools. In addressing the development of the era, the Bin Baz Islamic Center Boarding School has the nature of Tawasud/medieval